Cornstarch-coated activated carbon as a novel adsorbent for efficient detection of human norovirus in coastal shellfish - Ningbo Liao; Lu Ruan; Chengwei Liu; Yuexia Wang; Peng Tian; Ronghua Zhang; Guoping Wu (Food Control, 2026)

Study on particle fragmentation characteristics during rapid pyrolysis of coal based on the structural characteristics of coal macerals - Guoping Ma; Peng Lv; Xudong Song; Yonghui Bai; Jiaofei Wang; Weiguang Su; Guangsuo Yu (Fuel, 2026)

Insights into hydrography modulating population structure of the ocellated icefish (Chionodraco rastrospinosus) in the Bransfield Strait, Antarctica - Zukun Peng; Zhuang Chen; Lingqiao Cheng; Shuhao Ma; Guoping Zhu; Congcong Wang (Estuarine, Coastal and Shelf Science, 2026)

Head-to-head comparison of plasma biomarker assays across platforms for amyloid pathology in a multicenter cohort - Xinyi Lv; Kaiyuan Shen; Qianhua Zhao; Guoping Peng; Huayan Liu; Feng Gao; Xiaodong Pan; Wei Chen; Peilin Lu; Haining Zhang; Shuting Zhang; Mengya Xing; et al. (Science Bulletin, 2026)

The relationship between micro-fragmentation mechanisms and macro-mechanical responses in granite residual soil - Bingxiang Yuan; Xiangwen Deng; Peng Luo; Xueqiang Yang; Jim Shiau; Xiaoyu Bai; Mayao Cheng; Guoping Lei; Junjie Zheng (Transportation Geotechnics, 2026)

Role of mitochondrial biogenesis in methanol-induced neurobehavioral changes in rats - Guoping Li; Xiaohong Du; Xinqiao Wang; Xiaojie Han; Mengnan Peng; Chen Nan (Toxicology Letters, 2026)

Role of the AMPK/PGC-1α/SIRT3-Mediated Mitochondrial Dysfunction in the Neurotoxicity of Methanol - Xiaojie Han; Mengnan Peng; Xinqiao Wang; Yundi Hu; Guoping Li; Yanan Song; Yanling Lv; Nan Chen (Molecular Neurobiology, 2026)

Sensomics-metabolomics integration reveals key flavor compounds in black tea-Longhui Jinyinhua blends - Yingying Shen; Yangbo Xiao; Nan Xu; Guoping Peng; Xia Yin; Qiming Wang (Food Bioscience, 2025)

Inferring population structure of mackerel icefish (Champsocephalus gunnari) between South Orkney Islands shelf and South Georgia shelf, Antarctic using otolith ecomorphological analyses - Youfeng Peng; Guoping Zhu (Fisheries Research, 2025)

Innovative dry magnetic separation for Enhanced recovery of magnetic iron oxides from coal fly ash - Zeyu Zhang; Qijing Zhu; Guangfa Huang; Yaoji Chen; Jun Li; Guoping Zhao; Xiaoling Peng; Jing Li; Xinqing Wang (Fuel, 2025)

Fine mapping and identification of CqMYB62 as the subgynoecy gene in chieh-qua (Benincasa hispida Cogn. var. Chieh-qua How) - Yin Gao; Jiazhu Peng; Yanchun Qiao; Guoping Wang; Jianpo Zhan; Wensheng Zhang (Theoretical and Applied Genetics, 2025)

High temperature co-processing of basic oxygen furnace slag and blast furnace slag: Self-pulverization and reduction mechanism - Lan Huang; Shengli An; Fang Zhang; Jun Peng; Guoping Luo; Yuxin Chen; Yifan Chai (Process Safety and Environmental Protection, 2025)

Taraxasterol attenuates inflammatory responses in a 2,4-dinitrochlorobenzene-induced atopic dermatitis mouse model via inactivation of the MAPK and NF-κB pathways - Yu Zhang; Guoping Peng; Rusheng Zhang (Journal of Molecular Histology, 2025)

Microbial mechanisms of sulfate reduction for low-temperature bioremediation of acid-mined uranium sandstone groundwater - Rui Xiao; Zhenghua Liu; Min Xu; Guoping Jiang; Yang Peng; Cunzeng Li; Jie Wang; Huaqun Yin; Lechang Xu (Journal of Water Process Engineering, 2025)

Instantaneous detection and location of contaminant sources in intelligent buildings: A distributed Kalman filter scheme - Chen Ma; Aibing Qiu; Xiaojing Peng; Juping Gu; Guoping Lu (Energy and Buildings, 2024)

Molecular insights and functional analysis of isocitrate dehydrogenase in two gram-negative pathogenic bacteria - Wei Xiong; Rui Su; Xueyang Han; Mengxiao Zhu; Hongyiru Tang; Shiping Huang; Peng Wang; Guoping Zhu (World Journal of Microbiology and Biotechnology, 2024)

Sustainable finance in natural resource extraction: Navigating green recovery pathways - Bangyong Hu; Nianjiao Peng; Guoping Zhu (Resources Policy, 2024)

Effects of processing methods on the aroma of Poria cocos and its changing regulations during processing - Yangbo Xiao; Shu Liu; Luzhi Zeng; Churen Zhou; Yisi Peng; Yu Wu; Xia Yin; Guoping Peng (Food Chemistry, 2024)

Grapefruit essential oil combined with UV-C treatment: A technology to improve the microbial safety of fresh produce - Ningbo Liao; Xinyun Chen; Mengxuan Tang; Peng Tian; Chengwei Liu; Lu Ruan; Hong Pan; Mei Shu; Chan Zhong; Guoping Wu (Innovative Food Science & Emerging Technologies, 2024)

Simultaneous decontamination of phosphorus and bisphenol A from livestock wastewater with boehmite-modified carbon composite - Yaru Peng; Xiu Zhang; Yuan Luo; Azeem Muhammad; Guoping Yang; Kuok Ho Daniel Tang; Zengqiang Zhang; Yuan Xu; Menghao Li; Jintong Cui; Ronghua Li (Bioresource Technology, 2024)

Photochemical transformation of terrestrial dissolved organic matter derived from multiple sources in tropical plantations - Gege Yin; Peng Zhang; Yinghui Wang; Bilal Aftab; Penghui Du; Qiang Zhang; Guoping Chen; Mengke Wang; Biwei Yang; Senhao Wang; Jiangming Mo; Wei Zhang; et al. (Geochimica et Cosmochimica Acta, 2023)

Distinct resting-state functional connectivity patterns of Anterior Insula affected by smoking in mild cognitive impairment - Tianyi Zhang; Qingze Zeng; Kaicheng Li; Xiaocao Liu; Yanv Fu; Tiantian Qiu; Peiyu Huang; Xiao Luo; Zhirong Liu; Guoping Peng (Brain Imaging and Behavior, 2023)
Smoking is a modifiable risk factor for Alzheimer’s disease (AD). The insula plays a vital role in both smoking and cognition. However, the smoking effects on insula-related networks in cognitively normal controls (CN) and mild cognitive impairment (MCI) patients remain unknown. We identified 129 CN (85 non-smokers and 44 smokers) and 83 MCI (54 non-smokers and 29 smokers). Each underwent neuropsychological assessment and MRI (structural and resting-state functional). Seed-based functional analyses in the anterior and posterior insula were performed to calculate the functional connectivity (FC) with voxels in the whole brain. Mixed-effect analyses were performed to explore the interactive effects on smoking and cognitive status. Associations between FC and neuropsychological scales were assessed. Mixed-effect analyses revealed the FC differences between the right anterior insula (RAI) with the left middle temporal gyrus (LMTG) and that with the right inferior parietal lobule (RIPL) ( p < 0.01, cluster level < 0.05, two-tailed, gaussian random field correction). The FC of RAI in both LMTG and RIPL sees a significant decrease in MCI smokers ( p < 0.01). Smoking affects insula FC differently between MCI and CN, and could decrease the insula FC in MCI patients. Our study provides evidence of neural mechanisms between smoking and AD.

Dual role of soil-derived dissolved organic matter in the sulfamethoxazole oxidation by manganese dioxide - Biwei Yang; Penghui Du; Guoping Chen; Peng Zhang; Qiang Zhang; Zhongying Wang; Gan Zhang; Zongwei Cai; Junjian Wang (Water Research, 2023)

Use of bentonite-coated activated carbon for improving the sensitivity of RT-qPCR detection of norovirus from vegetables and fruits: The ISO 15216-1:2017 standard method extension - Mengxuan Tang; Ningbo Liao; Peng Tian; Kaisheng Shen; Chengwei Liu; Lu Ruan; Guoping Wu (Food Microbiology, 2023)

Soluble extracellular polymeric substance (SEPS) of histo-blood group antigen (HBGA) expressing bacterium Sphingobacterium sp. SC015 influences the survival and persistence of norovirus on lettuce - Ningbo Liao; Mengxuan Tang; Lili Chen; Peng Tian; Dapeng Wang; Dongqing Cheng; Guoping Wu (Food Microbiology, 2023)

Identification and Characterization of a Novel Soluble Pyridine Nucleotide Transhydrogenase from Streptomyces avermitilis - Zhengyu Cao; Jie Liu; Rui Meng; Peng Wang; Guoping Zhu (Current Microbiology, 2022)

Biochemical and phylogenetic characterization of a monomeric isocitrate dehydrogenase from a marine methanogenic archaeon Methanococcoides methylutens - Peng Wang; Yuan Wang; Xiuxiu Guo; Shiping Huang; Guoping Zhu (Extremophiles, 2020)

Regulating effect of CBF on memory in cognitively normal older adults with different ApoE genotype: the Alzheimer’s Disease Neuroimaging Initiative (ADNI) - Junyang Wang; Guoping Peng; Ping Liu; Xufei Tan; Benyan Luo (Cognitive Neurodynamics, 2019)

Comparison of two air temperature gridding methods over complex terrain in China - Guoping Shi; Zhian Sun; Xinfa Qiu; Yan Zeng; Peng Chen; Changjie Liu (Theoretical and Applied Climatology, 2018)

MicroRNA let-7e Is a Potential Circulating Biomarker of Acute Stage Ischemic Stroke - Guoping Peng; Yuan Yuan; Shanshan Wu; Fangping He; Yewen Hu; Benyan Luo (Translational Stroke Research, 2015)

Association between the IL7R T244I polymorphism and multiple sclerosis: a meta-analysis - Ruijie Zhang; Lian Duan; Yongshuai Jiang; Xuehong Zhang; Peng Sun; Jin Li; Mingming Zhang; Guoping Tang; Xing Wang; Xia Li (Molecular Biology Reports, 2011)

The Application of Intraoperative Ultrasound During Partial Hepatectomy for the Accurate Detection and Removal of Intrahepatic Bile Duct Stones - Guoping Xing; Gong Chen; Xiaobao Peng (Cell Biochemistry and Biophysics, 2011)